IDEOLOGI JILBAB - Ida Novianti (Jurnal Penelitian Agama, 2020)
Jilbab is a popular fashion of Indonesian female Muslims, worn by all social and educational levels as well as found in all geographical locations. This fact cannot be separated from the struggle of Muslim activists to popularize it. As a part of religious teaching, jilbab is closely related to the understanding and experience of Islam as a religion. However, in its real manifestation of wearing jilbab, religious considerations are not the only reasons for female Muslims to wear it. Jilbab has meant differently from time to time. Nowadays, various models of jilbab are easily found and the motives of its users vary and determine the model they choose. This fact leads to a typology of jilbab which is influenced by the need of its users.